Réflexion sur les liens entre féminisme et « lesbianisme » : la Maison des femmes de Toulouse - Justine Zeller (Les Cahiers de Framespa)
It’s a matter of taking an interest in the links between feminism and lesbianism by conducting a comparison between the national and local contexts (Toulouse). If the feminist activists (homosexuals and heterosexuals) meet in the Mouvement de libération des femmes (MLF), a lesbian separatism begins to emerge in Paris from 1971 and in many more cities during the decade, until the definitive break in 1979. But to Toulouse no autonomous lesbian group emerged during the period. If the activists of la Maison des femmes (important place of the toulousain women’s movement) are homosexual in the majority and say themselves sometimes lesbian, they consider as "women loving women" favoring of this fact the fights for the women’s rights and reflections on "woman’s identity". A lesbian movement develops in Toulouse during 1990s with the creation of Bagdam cafée become officially Badgam espace lesbien in 2001.